Analisis Penerapan Standar Operasional Prosedur Terhadap Kualitas Kinerja Karyawan pada Custom Gift Box di Purwokerto Jawa Tengah - Parlina, Fatma Iin; Fadhillah, Is (Ikatan Da'i Indonesia, 2024)
To the organization's goals, standard operational procedures (SOPs) require an approach to prevent and reduce errors and deviations in the performance of tasks. SOP is an administrative control model accompanied by supervision by the leadership or staff who acquire duties and functions. Employee performance is influenced by the implementation of Standard Operational Procedures (SOPs), where the work process is based on standards and criteria that have been previously established. Some of the facts still found in the field are: 1) product specifications do not match customer request specifications; 2) delays in delivery times; 3) uneven workloads of employees. Besides, there are activities that haven't run according to the instructions / short and there is still a waste of time on the production process. This research aims to describe the strategy of implementing Standard Operational Procedures in improving the quality of employee performance on Custom Gift Box in Purwokerto Central Java. The research approach used is qualitative where this approach produces findings obtained through data collected in a variety of ways, including interviews, observations, and documentation studies to gain an in-depth understanding of the problem rather than generalization. This research produces a description of the application of Standard Operational Procedures (SOP) production in Custom Gift Box in running the production process of making custom-boxes.In addition, the implementation of Standard Operations procedures in Custom Gift Boxes has an impact on improving the performance of employees in carrying out custom box making process through the awareness of owners and employees.